Equity in the utilisation of health care in Ireland - Layte, Richard; Nolan, Brian (Economic & Social Studies, 2004)
This paper analyses the extent of equity of health service delivery across the income distribution in Ireland ? that is the extent to which there is equal treatment for equal need irrespective of income. We find that almost all services, apart from dental and optician services, are used more by those at the lower end of the income distribution, but that this group also have the greatest need for health care. The comparison of health need to health care delivery across the income distribution without standardising for confounding factors suggests that those in higher income groups receive more health care for a given health status indicating inequity. However, need for health care is highest among the elderly and this group also tend to be at the bottom of the income distribution. Once we standardise for age, sex and location we find that hospital services are distributed equitably across the income distribution, whereas GP and prescription services tend to be pro-poor (used more by those with lower incomes for a given health status) and dental and optician services tend to be pro-rich (used more by those with higher incomes for a given health status).
Keywords: Health services; Equity; Ireland; Income distribution